2010
DOI: 10.1029/2010jc006297
|View full text |Cite
|
Sign up to set email alerts
|

Temperature inversion in China seas

Abstract: [1] Temperature inversion was reported as a common phenomenon in the areas near the southeastern Chinese coast (region A), west and south of the Korean Peninsula (region B), and north and east of the Shandong Peninsula (region C) during October-May in the present study, based on hydrographic data archived from 1930 through 2001 (319,029 profiles). The inversion was found to be remarkable with obvious temporal and spatial variabilities in both magnitude and coverage, with higher probabilities in region A (up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…Although temperature usually decreases with increasing depth, this normal temperature profile is not always maintained in the YS. Temperature inversion is a phenomenon where the temperature at deeper depths is higher than that at shallower depths, and this has been seen to frequently occur in two areas around the Shandong Peninsula and southwest of the Korean Peninsula [ Kim et al ., ; Hao et al ., ]. Recently, Lie et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although temperature usually decreases with increasing depth, this normal temperature profile is not always maintained in the YS. Temperature inversion is a phenomenon where the temperature at deeper depths is higher than that at shallower depths, and this has been seen to frequently occur in two areas around the Shandong Peninsula and southwest of the Korean Peninsula [ Kim et al ., ; Hao et al ., ]. Recently, Lie et al .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies based on limited in situ hydrographic data showed that a temperature inversion is frequently observed in the thermohaline frontal area southwest of Korea during wintertime [ Kim et al ., ; Hao et al ., ; Lie et al ., ]. In this paper, we reveal how the temperature inversion evolves during wintertime when northerly winds prevail over the YS, and explain the dynamics associated with ocean circulations driven by surface wind forcing.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The presence of a temperature inversion can be a manifestation of the prevailing ocean circulation over a region, and therefore an understanding of the structure and mechanism causing temperature inversions is necessary to realistically explain physical processes in oceanic regions. A temperature inversion has been frequently observed during winter in the thermohaline frontal area southwest of Korea [ Kim et al ., ; Hao et al ., ; Lie et al ., ]. Based on a Korean serial hydrographic data set (1965–1979), Kim et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at some depths, the water temperature of the middle and lower layers sometimes rises above that of the upper layer, which is called a water temperature inversion (TI). The causes of this water temperature inversion layer (TIL) may be due to: (1) Near heat loss from the sea surface [1], (2) wind-driven current moving from a cold water area to a warm water area [2], and (3) mixing process in the front area [3]. A TIL mainly occurs in coastal upwelling areas [4] and in polar fronts [3], where different water masses meet, and complex marine physical characteristics, such as water temperature fronts, are found near the boundaries of these areas [5].…”
Section: Introductionmentioning
confidence: 99%